Analisis Faktor-Faktor yang Mempengaruhi Hasil Panen Padi Oryza sativa L - Ardian (Journal of Geographical Sciences and Education, 2024)
Considering that rice acts as the main food ingredient, the availability of rice plays a key role in achieving national food security. This research aims to analyze the factors that influence rice yields through literature studies. This research was carried out by reading relevant sources to obtain the necessary data. The data used in this research is secondary data which is analyzed and related to research variables. The research results show that the factor that greatly influences rice harvest is the land area variable. Meanwhile, the influencing variables is labor. Urea fertilizer, capital, experience and production are considered to have quite an influence on rice yields.